Solo leveling. 7 - Ch'ugong; h-goon (Anime creator) (Ize Press, 2023)
"The Jeju Island raid is underway, and the elite team of Korean hunters has finally come face-to-face with the ant queen! Soon, Jeju Island would be theirs to reclaim from the magic beasts after four long years--or so they thought. Little did they know that her strongest soldier would be unlike any magic beast they'd ever fought before!"--